Interpreting Arabic-Indonesian Grammatical Linguistic Symbols in Yellow Book Learning: Semiotic Analysis - Alamin, Fajar; Sopian, Asep; Nursyamsiah, Nunung (Institut Agama Islam Negeri Curup, 2024)
The grammatical linguistic symbols (GLS) are used in teaching yellow book (kitab kuning /traditional Islamic texts) and Arabic grammar in traditional Islamic boarding schools using regional languages such as Javanese and Sundanese, and are beginning to be adopted in the Indonesian language. This study aims to explore their usage practices in the latter language while examining their benefits, limitations, and impacts. This research novelty lies in its focus on the Indonesian language, considering that previous studies on GLS primarily focused on regional languages. The research method employed is descriptive qualitative, utilizing observation, interviews, and tests as instruments at Pondok Tahfidz Zawiyah Darul Hayat. The observational and interview data are analyzed using Saussure's semiotics theory. The test results are used to determine the impact of using GLS. This study investigates the use of GLS in Indonesian and examines its advantages, drawbacks, and effects. The results show that GLS is useful for comprehending yellow book grammatical functions, particularly those related to syntax, fa'idah, and word abbreviations. Notwithstanding its benefits, GLS isn't universally applicable and might cause mistakes, particularly when choosing symbols. Test results indicate that GLS helps with grammatical position determination. In an effort to address these limitations, the research recommends the creation of a standardized guidebook explaining the use of GLS and the addition of new symbols to support uncovered grammatical functions. This study makes a substantial contribution to the preservation of local knowledge in the context of Indonesian Islamic boarding schools, especially with regard to Arabic grammar teaching. By examining this aspect, the study enriches understanding not only of language dynamics but also of cultural preservation and educational practices in Indonesia.